Spatial Planning for Resilient Economic Diversification : La Guajira, Colombia - Dobbin, James; Marquez, Tatiana; Rietbergen-McCracken, Jennifer (Washington, DC: World Bank, 2021)
As the world moves away from fossil fuels, mining-dependent regions that once provided the foundation for employment and economic growth now face the post-mining prospect of economic shock and social upheaval. Economic diversification of these regions is a huge challenge that needs to be addressed as a matter of urgency to enable their transition to a sustainable growth path. "Spatial Planning for Resilient Economic Diversification: La Guajira, Colombia" describes how strategic spatial planning can be used to gain new insights of opportunities and constraints for mining-dependent regions and to develop multisectoral development plans for resilient and sustainable economies. The planning approach, which has been used in a wide range of mining-related contexts, focuses on identifying and exploiting intersectoral synergies to develop interventions that together offer large-scale employment and economic benefits. The report features a recent spatial planning exercise commissioned by the Cerrejón coal mine in La Guajira, Colombia, with additional illustrations from recent applications of the same planning approach in Africa. The case in La Guajira is striking. The local economy is heavily dependent on the Cerrejón mine, one of the world’s largest coal mining operations, while most of the population rely on subsistence agriculture. With its high levels of poverty, harsh environment, and complex social dynamics, La Guajira faces enormous challenges. Yet the planning work reveals high potential opportunities in renewable energy, agricultural development, tourism, and a variety of other sectors. The report offers a methodology for data-led development planning that will be of interest to policy makers, policy advisers, donors, and the private sector on themes related to shared value creation, collaborative development planning, planning for mine closure and post-closure, and planning for a low-carbon economy.